Effect of Water-Soluble Echinochrome Analog on Arrhythmia Severity in Experimental Model of Acute Myocardial Ischemia - Bernikova, O G; Sedova, K A; Kharin, S N; Azarov, Ya E (Bulletin of experimental biology and medicine, 2018)
The effects of therapeutic or preventive-therapeutic administration of water-soluble echinochrome analog U-441 on arrhythmia severity assessed by a set of myocardial spatio-temporal depolarization and repolarization parameters were examined on the model of acute myocardial ischemia in cats. Coronary occlusion increased activation time and decreased repolarization time in the ischemic zone; in addition, it increased both global and borderline (local) dispersions of repolarization. The linear regression model showed that only activation time values measured at the initial state and at termination of occlusion were associated with total arrhythmia score during ischemia (regression coefficient β=0.338, 95%CI=0.074-0.602, p=0.015 and β=0.720, 95%CI=0.323-1.117, p=0.001, respectively). The study revealed no association between administration of echinochrome analog U-441 and arrhythmia severity.
Keywords: Sea Urchins; Coronary Occlusion; kočky; Heart Conduction System; Electrocardiography; koronární okluze; ischemia; modely nemocí na zvířatech; rozpustnost; převodní systém srdeční; zvířata; ježovky; echinochrome analog U-441; stupeň závažnosti nemoci; Myocardial Ischemia; srdeční arytmie; Naphthoquinones; voda; antiarytmika; Solubility; ischemická choroba srdeční; Anti-Arrhythmia Agents; Severity of Illness Index; cats; ventricular arrhythmias; myokard; Arrhythmias, Cardiac; naftochinony; Animals; Cats; Water; Myocardium; Treatment Failure; Disease Models, Animal; predictors; neúspěšná terapie; elektrokardiografie